2021
DOI: 10.1002/adfm.202109176
|View full text |Cite
|
Sign up to set email alerts
|

Sulfation of Glycosaminoglycan Hydrogels Instructs Cell Fate and Chondral versus Endochondral Lineage Decision of Skeletal Stem Cells In Vivo

Abstract: Exit from multipotency and lineage commitment of mesenchymal stroma cells (MSC) depends on microenvironmental cues from the stem‐cell niche but steering cell fate into the desired lineage in vivo remains a challenge. Increasing evidence suggests that glycosaminoglycans (GAGs) can be used to activate or sequester growth factors with the specific action depending on sulfation levels. It is postulated that differentially sulfated biomaterials can aid developmental lineage instruction of MSC to guide tissue morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…In contrast to the report by Occhetta et al, the more recent data demonstrated that endochondral MSC misdifferentiation occurred independently of BMP-ALK1/2/3 activity (here and [27]). Neither ALK1/2/3 inhibitor was able to induce the desired chondral lineage shift, which is defined by strong chondrocyte formation without accompanying signs of hypertrophy, and which can be induced at least partially in vitro with pulsed PTHRP treatment or WNT inhibition or fully in vivo with heparin-coupled TGF-β [5,6,10]. When LDN-193189 was used in low doses that are expected to repress ALK1/2/3 but not ALK4/5, no effect on MSC chondrogenesis was observed by Franco et al in line with the small effects observed here with compound A and LDN21 [23,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the report by Occhetta et al, the more recent data demonstrated that endochondral MSC misdifferentiation occurred independently of BMP-ALK1/2/3 activity (here and [27]). Neither ALK1/2/3 inhibitor was able to induce the desired chondral lineage shift, which is defined by strong chondrocyte formation without accompanying signs of hypertrophy, and which can be induced at least partially in vitro with pulsed PTHRP treatment or WNT inhibition or fully in vivo with heparin-coupled TGF-β [5,6,10]. When LDN-193189 was used in low doses that are expected to repress ALK1/2/3 but not ALK4/5, no effect on MSC chondrogenesis was observed by Franco et al in line with the small effects observed here with compound A and LDN21 [23,27].…”
Section: Discussionmentioning
confidence: 99%
“…Expressing Indian hedgehog (IHH), type X collagen, alkaline phosphatase (ALP), osteopontin (OPN or SPP1) and other typical markers, hypertrophic chondrocytes exhibit an undesirable mineralization activity and a strong tendency to degenerate and induce bone formation at ectopic sites in vivo [2][3][4]. In our recent break-through study, a novel heparin-equipped biomaterial augmented with transforming growth factor (TGF)-β allowed stable chondral lineage commitment of MSCs in an in vivo setting [5]. In vitro, however, our continuing inability to induce stable chondral MSC differentiation shows that our understanding of the specific molecular events that are necessary to stabilize the chondrocyte phenotype still remains incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…For Western blot detection of collagen type II and collagen type X, collagens were isolated using the pepsin isolation method according to [ 26 ]. In brief, constructs were digested in pepsin solution (2.5 mg/mL pepsin in 0.5 M acetic acid, 0.2 M NaCl pepsin buffer) for at least 16 h at room temperature to degrade all proteins except collagens.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike AC, MSC undergo endochondral differentiation into hypertrophic chondrocytes in vitro, and MSC-based neocartilage can mineralize and develop into bone in vivo [ 25 , 26 ]. Two studies investigated the effect of elevated extracellular calcium levels on chondrogenesis of human chondroprogenitor cells in 3D culture.…”
Section: Introductionmentioning
confidence: 99%
“…Chasan et al developed an injectable TGF-𝛽-loaded heparin-PEG-hydrogel and investigated the effect of heparin sulfation status on SSC fate in vivo. [260] Hydrogels containing heparin (fully sulfated) and selectively 6-O/N-desulfated heparin (34% ± 5.6% sulfation level relative to heparin) were prepared separately. It was demonstrated in this study that the fully sulfated heparin dramatically prolonged the TGF-𝛽 retention time in the hydrogel and suppressed Hedgehog-, BMP-, and WNT-pathways.…”
Section: Heparinmentioning
confidence: 99%